Analisis Beban Kerja Mental Dengan Metode NASA-TLX Pada Karyawan UD. XYZ - Iztihar, Jauhara; Chandra, Huki; Wahyuni, Ayu Endah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Mental workload is a condition where the demands of mental work exceed the brain’s capacity to fulfill them. This situation can lead to various issues such as stress, fatigue, and a decline in performance. This study aims to measure the mental workload of UD. XYZ employees using the NASA-TLX method. This method is employed to  subjectively measure mental workload and is  known for its effectiveness in considering factors like task demands, fatigue, and  stress levels. The research involved 40 UD.XYZ employees who completed the NASA-TLX questionnaire. Data collection took place from October 2023 to March 2024, and the collected data  were processed and analyzed. The results of the mental workload measurement using NASA-TLX can be utilized to  evaluate the level of workload on UD.XYZ employees. Additionally, the study seeks to identify which factors from the NASA-TLX dimensions have the most significant impact on the occurrence of mental workload. The findings are expected to provide recommendations to UD.XYZ management for developing strategies to minimize excessive mental workload among employees.